Optimizing UI/UX of AIMsCORE Application with Design Thinking to Enhance User Interaction and Engagement - Jannatunnisa; Abdul Rahim; Sayekti Harits Suryawan (Teknika, 2025)
The AIMsCORE student assessment application at the AIK and MKDU Institute faces challenges in terms of interface and user experience, including unresponsive design, unintuitive navigation, and reliance on administrators for grade updates. This study aims to optimize AIMsCORE's UI/UX using the Design Thinking approach (empathize, define, ideate, prototype, testing) and usability measurement through the Single Ease Question (SEQ). In the empathize phase, in-depth interviews were conducted with 15 informants, including institutional leaders, lecturers, and administrative staff. Data were validated through triangulation comparing information from multiple sources and perspectives to ensure objectivity and minimize bias. This method strengthens data credibility and informs problem-based solution design. SEQ was used to assess usability, measuring user difficulty in interacting with the prototype. Results show improved usability: ease of use rose by 6.15% (from 65 to 69), visual design increased by 25% (from 56 to 70), and user expectation alignment improved by 18.03% (from 61 to 72). New features such as grade import and real-time notifications enhanced efficiency and user satisfaction. This study offers practical insights for institutions and organizations seeking to develop responsive, data-driven academic applications grounded in user-centered UI/UX principles.